Pengaruh Konseling Realitas untuk Menurunkan Kecemasan Istri Pasca Bercerai di Desa Bolo Ujungpangkah Kabupaten Gresik (Jurusan Bimbingan dan Konseling Islam, 2017)
The research focus is : is there any influence of reality counseling to decrease ex-wife’s anxiousness after divorce in Bolo Ujungpangkah Gresik ? In answering this problem, this research used Quantitative approach because the data that were taken by the researcher are in numerical data that had been processed statically. It also described deductively according to the theory and observation. For checking the validity of the theory the researcher draws the conclusion. Therefore it described descriptively because the result would be purposed to describe the data taken to answer the research problem. This research genre are field research and liyeratire study, it based on the place that the data taken. Whereas study literature used for collecting the data from some sources that related to the problem which was discussed in this research. Field research used to collecting data from the object, it can be quantitatively or qualitatively that are needed. This research also used survey research technique because did not use any changing to the variable. For the data analysis technique, this research used product moment formula. The result of this research is “r table” bigger than “r hitung”, so the hypotheses is no influence of reality counseling to decrease ax-wife’s anxiousness after divorce in Bolo Ujungpangkah Gresik. It can be concluded based on the result if “r table” bigger than “r hitung.